INDUSTRIAL ENGINEERING - Carrion N., José Luis (2001)
The origins of industrial engineering dating from the eighteenth century and are associated with the industrial revolution that occurred in Britain with the advent of the steam engine. Engineers habíanse become owners and managers, their subordinates demanded greater attention to economic problems.